Determinants of Appropriate Child Health and Nutrition Practices among Women in Rural Gambia - Mwangome, Martha; Prentice, Andrew; Plugge, Emma; Nweneka, Chidi (Journal of Health, Population and Nutrition, 2010)
Health education and awareness involves providing knowledge about causes of illness and choices to promote a change in individual behaviour and, thus, improves survival of individuals. Studies have, however, shown that improved knowledge and awareness is not always translated into appropriate actions. This study aimed at exploring the factors determining mothers' choices of appropriate child health and nutrition practices in the Gambia. Eight focus-group discussions (FGDs) were held with 63 women whose children had been seen at the Keneba MRC Clinic within the 12 months preceding the study. The FGDs were analyzed using a thematic framework. Gender inequality, presence or absence of support networks, alternative explanatory models of malnutrition, and poverty were identified as the main factors that would determine the ability of a mother to practise what she knows about child health and nutrition. The findings highlight the need to consider the broader social, cultural and economic factors, including the value of involving men in childcare, when designing nutritional interventions. Key words: Child health; Child nutrition; Child nutrition disorders; Gender; Health education; Interventions; Knowledge, attitudes, practices; The Gambia DOI: 10.3329/jhpn.v28i2.4887 J Health Popul Nutr 2010 Apr; 28(2): 167-172